М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
Пензик
Пензик
30.07.2020 21:05 •  Алгебра

Решить уравнение (дробь) (x-1)(x^2-2^2)(x^4-4^4)(x^8-8^8) = 0 x^2-6x+8 ^ - степень

👇
Ответ:
ask52
ask52
30.07.2020
(x -1)(x² -2²)(x^4 -4^4)(x^ -8^8)/(x² -6x +8) =0 ;
ОДЗ : x∈(-∞;2)U (2;4) U(4;∞).
(x-1)(x-2)(x+2)(x -4)(x+4)(x²+4²)(x  + 8)(x-8)(x²+8²)(x^4+8^4)/(x-2)(x-4) =0 ;
(x-1)(x+2)(x+4)(x+8)(x-8) =0 ;

ответ :  { -8; -4 ; -2 ; 1 ; 8}.
4,8(25 оценок)
Ответ:
битика
битика
30.07.2020
X²-6x+8≠0
x1+x2=6 u x1*x2=8
x1≠2 U x2≠4
x-1=0⇒x=1
x²-2²=0⇒x²=2²⇒x=-2 U x=2-не удов усл
x^4-4^4=0⇒x^4=4^4⇒x=-4 U x=4 не удов усл
x^8-8^8=0⇒x=-8 U x=8
x={-8;-4;-2;1;8}
4,6(44 оценок)
Открыть все ответы
Ответ:
Terraria10299
Terraria10299
30.07.2020
1) x²-6x+8=0
x²-6x=-8
x²-6x+9=-8+9
(x-3)²=1
x-3=1   x-3=-1
x₁=4      x₂=2
4*2=8
4+3=6
2) x²+2x-3=0
x²+2x=3
x²+2x+1=3+1
(x+1)²=4
x+1=2    x+1=-2
x₁=1       x₂=-3
1*(-3)=-3
1+(-3)= 1-3=-2
3) x²-5x+6=0
x²-5x=-6
x²-5x+6,25=-6+6,25
(x-2,5)²=0,25
x-2,5=0,25    x-2,5=-0,25
x₁=2,75         x₂=2,25
2,75*2,25=6,1875
2,75+2,25=5
4) x²-6x+5=0
x²-6x=-5
x²-6x+9=-5+9
(x-3)²=4
x-3=2     x-3=-2
x₁=5       x₂= 1
5*1=5
5+1=6
5) x²-7x+2=0
x²-7x=-2
x²-7x+12,25=-2+12,25
(x-3,5)²=10,25
x-3,5=√0,41/2       x-3,5=-√0 ,41/2
x₁= √0,41+7 /2      x₂=-√0,41+7 /2
√0,41+7/2+(-√0,41+7/ 2) = 1/2
6) x²-x-30=0
x²-x=30
x²-x+0,25=30+0,25
(x-0,5)²=30,25
x-0,5=5,5      x-0,5=-5,5
x₁=6               x₂= -5
6*(-5)=-30
6+(-5)= 6-5=1
4,6(74 оценок)
Ответ:
мирас68
мирас68
30.07.2020

Вот накалякал. Разбирайся :)

xy/(x+y) = 5
xz/(x+z) = 7
yz/(y+z) = 9

xy = 5x + 5y
xz = 7x + 7z
yz = 9y + 9z

x(y-5) = 5y
x = 5y/(y-5)


5yz/(y-5) = 35y/(y-5) + 7z
5yz = 35y + 7z * (y-5)
5yz = 35y + 7yz - 35z
2yz + 35y = 35z
y(2z + 35) = 35z
y = 35z/(2z + 35) = z/(2z/35 + 1)

35z^2/(2z + 35) = 315z/(2z + 35) + 9z
35z^2 = 315z + 9z*(2z + 35)
35z^2 = 315z + 18z^2 + 315z
17z^2 = 630z
z=630/17

y = 35*630/(2*630/17 + 35)/17 = 35*630/(1260 + 595) = 22050/1855 = 630 / 53

x = 5*630/(630/53 - 5)/53  =  5*630/((630/53 - 5)*53) = 5*630/365 = 630/73

4,5(5 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ